CULTURAL HERITAGE OF EARLY KASHMIR-A STUDY - RASHID MANZOOR BHAT (RADJA PUBLIKA, 2022)
The cultural history of Kashmir can be explained in part by its geographical position. Because of Kashmir's natural beauty and moderate climate, it's possible that Kashmiris have a long history of artistic expression. As a result of Kashmir's seclusion, security afforded by the surrounding mountains, and its distance from the centre of Indian culture, Kashmiri philosophy might be unique. Because of the harsh weather and long winters, it's possible that Kashmiris are drawn to philosophical inquiry. The geographic centre of the Puranic world is Kashmir. In this system, Kashmir's significance was recognised as a meeting ground for trade and ideas between the four major regions of the Old World. For the first time ever, the land of opposites attempted to be reconciled through a deeper examination and a more ambitious notion. The study is an attempt to explore the rich cultural heritage of Kashmir in an analytical manner.